Uruguay : 2011 Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
This 2011 Article IV Consultation-Selected Issues paper focuses on estimating potential output and the output gap and spillovers from agriculture in the case of Uruguay. It introduces additional economic information and theory to estimate potential output, shedding some light on the discussion of current monetary and fiscal policies. The objective is to take advantage of economic data to disentangle the most recent economic performance by introducing multivariate techniques. The paper also presents an overview of the labor market and pension system of Uruguay.